ANALISIS PERANCANGAN STRUKTUR ORGANISASI PENYELENGGARAAN PROYEK PEMBANGUNAN PELABUHAN PATIMBAN - Wati, Wilda; Sakti, Wahyu Indra (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2018)
The need for construction of new ports in Indonesia these days has encouraged the Indonesian government to plan the National Strategic Project, namely the construction and development of Patimban Port as an International Port located in Subang Regency, West Java. The goal is to support the Tanjung Priok Port which is currently considered to be saturated and is also expected to reduce the cost of national logistics. In implementing the project, proper human resource management is needed, especially in terms of designing the organizational structure of the project. Thus, the purpose of this research is to identify the form of organizational structure of the project, identify the roles and relationships of each stakeholder shown in the organizational structure of the Patimban Port construction project in stage 1-1. This research uses descriptive qualitative approach. Data collection was carried out by literature studies, documentation, participant observation, data gathering and in-depth interviews. The design result shows that the organizational structure of the Patimban Port project is in the form of a line, that is, the relationship of the work provider and the executor of the work is still one line of authority. The stakeholders identified in the project organizational structure are the President of the Republic of Indonesia, the Prime Minister of Japan, the Ministry of Transportation of the Republic of Indonesia, the Ministry of Transportation of Japan, other related Ministries of the Republic of Indonesia, Patimban Port Work Unit, planning consultants, land procurement teams, auction teams, bridge contractors, port terminal contractors, breakwater contractors and supervisory consultants. Each stakeholder has an important role and relationship with one another in the implementation of the Patimban Port construction project.Keywords: Port, Patimban Port, Human Resource Management, Project Organizational StructureKebutuhan pengembangan pembangunan pelabuhan baru di Indonesia dewasa ini, mendorong pemerintah RI untuk merencanakan Proyek Startegis Nasional yaitu pembangunan dan pengembangan Pelabuhan Patimban sebagai Pelabuhan Internasioanl yang berlokasi di Kabupaten Subang, Jawa Barat. Tujuannya yaitu sebagai penyangga Pelabuhan Tanjung Priok yang saat ini telah dinilai jenuh dan juga diharapkan dapat menekan biaya logistik Nasional. Dalam penyelenggaraan proyek tersebut, dibutuhkan manajemen sumber daya manusia yang baik, terutama dalam hal perancangan struktur organisasi proyek. Sehingga, tujuan dari penelitian ini adalah mengidentifikasi bentuk struktur organisasi proyek, mengidentifikasi peranan serta hubungan masing – masing stakeholders yang ditunjukkan dalam struktur organisasi proyek pembangunan Pelabuhan Patimban pada tahap 1-1. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Pengumpulan data dilakukan dengan studi literatur, dokumentasi, observasi terlibat, penjaringan data dan wawancara mendalam. Hasil perancangan menunjukkan bahwa bentuk struktur organisasi proyek Pelabuhan Patimban berbentuk lini yaitu hubungan penyedia pekerjaan dengan pelaksana pekerjaan masih bersifat satu garis wewenang. Stakeholders yang teridentifikasi dalam struktur organisasi proyek yaitu Presiden RI, Perdana Menteri Jepang, Kementerian Perhubungan RI, Kementerian Perhubungan Jepang, Kementerian RI terkait lainnya, Satuan Kerja Pelabuhan Patimban, konsultan perencana, tim pengadaan tanah, tim pelelangan, kontraktor jembatan, kontraktor terminal pelabuhan dan kontraktor  breakwater dan konsultan pengawas. Setiap stakeholders memiliki peranan penting serta hubungan satu dengan lainnya dalam penyelenggaraan proyek pembangunan Pelabuhan Patimban.Kata Kunci: Pelabuhan, Pelabuhan Patimban, Manajemen Sumber Daya Manusia, Struktur Organisasi Proyek